All Days 2010
DOI: 10.2118/132003-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Trials of a Novel Fiber-Laden Self-Diverting Acid System for Carbonates in Saudi Arabia

Abstract: Acid stimulation of carbonate formations using hydrochloric (HCl) acid-based systems to improve hydrocarbon production or water injection has been a common practice since the early days of the oil and gas industry. The challenge of achieving full zonal coverage with the stimulation fluid still persists. This task is even more difficult in highly slanted layered, naturally fractured reservoirs exhibiting high permeability and porosity contrast.During acid stimulation treatments, the fluid has a natural tendency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the case of an OH completion, additional leakoff through the OH section between packers will further worsen the situation. Introduction of fiber-enhanced viscoelastic diverter for acid fracturing treatments helped address this challenge by keeping BHTP above fracturing extension pressure during most of the acid fracturing treatment time (Al-Ismail et al 2008;Jairo et al 2010, Jairo et al 2011Bukovac et al 2012). • When a large horizontal OH section isolated in between two packers is treated, the fracture initiates at the point of local min .…”
Section: Introduction and Problem Identificationmentioning
confidence: 99%
“…In the case of an OH completion, additional leakoff through the OH section between packers will further worsen the situation. Introduction of fiber-enhanced viscoelastic diverter for acid fracturing treatments helped address this challenge by keeping BHTP above fracturing extension pressure during most of the acid fracturing treatment time (Al-Ismail et al 2008;Jairo et al 2010, Jairo et al 2011Bukovac et al 2012). • When a large horizontal OH section isolated in between two packers is treated, the fracture initiates at the point of local min .…”
Section: Introduction and Problem Identificationmentioning
confidence: 99%
“…FVSDA has multiple benefits over PSDA: it is non-damaging to the reservoir and has a stable viscosity gain while acid spends, higher diverting efficiency in matrix and fissures due to stable viscosity and degradable fibers, fracture-tofracture diversion, and some others. Previously published papers (Al-Ismail et al 2008;Leal Jauregui et al 2010;Leal Jauregui et al 2011;Bukovac et al 2012) already showed the efficiency of this diverter for the carbonate formation. Figures 12 and 13 show normalized PI values for vertical and horizontal wells, respectively.…”
Section: Diverter Typementioning
confidence: 96%